In‐Situ Growth Mirror‐Like Cobalt Sulfide Nanosheets on ITO for High Efficiency Counter Electrode of Dye‐Sensitized Solar Cells. Issue 29 (11th August 2021) - Sun, Xun; Xie, Fengyan; Peng, Zhen; Peng, Xiantao; Chen, Wangchao; Shi, Chengwu; Chen, Caiyun; Li, Yafeng; Wei, Mingdeng
Abstract: In this work, mirror‐like Co9 S8 nanosheets in‐situ grown on indium tin oxide (ITO) glass substrate have been synthesized through a facile hydrothermal method and used as a novel Pt‐free counter electrode (CE) for dye‐sensitized solar cells. Based on mirror effect of the Co9 S8 CE, incident light has been efficiently utilization. As a result, the cell using Co9 S8 nanosheets CE achieved a power conversion efficiency of 9.01 %, which is higher than that of Pt CE. This could be contributed to the fact that mirror‐like Co9 S8 nanosheets exhibited an excellent catalytic activity for the reduction of I3 − /I − . Abstract : Mirror‐like Co9 S8 nanosheets were successfully in‐situ grown on indium tin oxide (ITO) glass substrate through a facile hydrothermal method, which could be used as counter electrode in dye‐sensitized solar cells (DSSCs) without any post treatment. DSSC base on the mirror‐like Co9 S8 nanosheets counter electrode achieved a high efficiency of 9.01 %